RELATIONSHIP OF HEALTH CARE QUALITY WITH BPJS PATIENT’S SATISFACTION - Lailatul Maghfiroh Adawiyah; Sri Sayekti; Bambang Tutuko (STIKES Insan Cendekia Medika Jombang, 2011)
Increased public awareness of health, will lead to increased demands for health services. Currently the Indonesian government has made a national policy by issuing a new program that is BPJS (Social Security Agency of Health). The increasing demand for quality public health services, the service function needs to be improved to give satisfaction for BPJS patient. The purpose of this study to determine the relationship of health care quality with BPJS patient’s satisfaction. The research used analitical design with a cross sectional approach, the population were all patients of BPJS user in RSI Sakinah Mojokerto with total sample as many 100 which conducted with simple random sampling technique. Independent variabel was the quality of health care and the dependent variabel was the BPJS patient’s satifaction. Measuring instrumemts used in this study was a questionnaire. Then, data was analyzed with spearman’s correlation statistical test with value p = 0.000 < α=0.05.This result was mostly respondents assessed the quality of health care was good (56.0%), good enough (44.0%) and BPJS patients satisfaction was quite satisfied (51.0%), satisfied (49.0%).The Spearman correlation statistical test results (p=0.000<α0.05) so that Ha accepted. The conclusion of this research obtained that there was significant relationship between quality of health care with BPJS patients satisfaction.